DETERMINATION OF ANTIOXIDANT CAPACITY OF RICEBERRY AND KHAO DOK MALI 105 CULTIVARS - pinwattana, Kulwadee; Sueaman, Kanjana; Paksee, Samaiporn; Arpsuwan, Aphinya; Sam-ang, Pornpat; Jannoey, Panatda; Chalongsuppunyoo, Rapikorn (PSRU Journal of Science and Technology, 2019)
The propose of this research was to determine and compare the antioxidant properties of brown rice and colorless brown rice with germination and cooking process. The 2,2-diphenyl-1- picrylhydrazyl was employed to analyze the antioxidant capacity. It was found that the Riceberry cultivar with red-purple color showed the antioxidant capacity higher than Khao Dok Mali 105 cultivar (KDML 105). The antioxidant value was found to be TEAC 883.03 of Riceberry cultivar and 690.14 μmol/g of KDML105 cultivars, respectively. The cooking process was applied to rice of both cultivars, it was found this process reduces the antioxidant capacity to 3.57% and 3.81% of cooked Riceberry and cooked KDML105 cultivar, respectively. Moreover, both cultivars were germinated by soaked for 12 hours and allow to germination for 2 days. The antioxidant capacity of both cultivars (Germinated Riceberry and Germinated KDML105) was decreased after the germination process. However, germinated and cooked Riceberry contains the antioxidant activity higher than germinated and cooked KDML105 at the ratio of 2.16 folds. Suggested that, anthocyanin compound which found in red-purple color rice of Riceberry cultivar may enhance the antioxidant activity of color rice. Moreover, the germination process in this study does not affect to increase the antioxidant activity, while the cooling process will reduce the antioxidant activity of both cultivars.